Increasing Repurchase Intention through Product Quality and Pricing Strategy: A Fast-Food Sector Analysis - Suryani, Yosi; Miranda, Deva Dwi; Gustiawan, Willson (Economics, Business, Accounting & Society Review, 2024)
In today's competitive culinary market, repurchase intention serves as a key determinant of business profitability and sustainability. This study analyzes the impact of product quality and price on repurchase intention in the context of the fast-food sector, "Ayam Tokok Balenggek", a traditional chicken-based dish from West Sumatra, Indonesia. This paper used data from 100 respondents, the research investigates the partial and simultaneous effects of product quality and price on customer loyalty and repeat purchasing behavior. The findings reveal that product quality significantly influences repurchase intention by meeting or exceeding customer expectations in terms of taste, texture, and overall satisfaction. Similarly, competitive and affordable pricing enhances perceived value, fostering trust and encouraging repurchases. The results highlight the critical role of maintaining high-quality standards and implementing fair pricing strategies to strengthen customer retention and drive business growth. This study contributes to the field by offering actionable insights for small businesses in the culinary sector, demonstrating how a balanced focus on quality and price can enhance customer loyalty, improve brand competitiveness, and ensure long-term sustainability. These findings provide a foundation for Ayam Tokok Balenggek to optimize its product offerings and pricing policies to align with customer expectations and market demands.